2015
DOI: 10.1626/pps.18.491
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Oil Palm Empty Fruit Bunch Biochar on Floodwater pH and Yield Components of Rice Cultivated on Acid Sulphate Soil under Rice Intensification Practices

Abstract: Rice has a vital role in food security but the production is limited in infertile and degraded soils. Rice is cultivated on acid sulphate soil in the coastal area of Peninsular Malaysia. Soil amendment using biological charcoal (biochar) increases the soil fertility. Thus, empty fruit bunch biochar (EFBB) was applied in a pot experiment under a controlled environment using an organic system of rice intensification (SRI) practice and its effects on the floodwater pH, acid sulphate soil properties and growth per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 45 publications
2
14
0
Order By: Relevance
“…It is well-known that amendment of biochar to croplands can enhance crop productivity Bakar et al, 2015). As showed in Figs.…”
Section: Discussionmentioning
confidence: 93%
“…It is well-known that amendment of biochar to croplands can enhance crop productivity Bakar et al, 2015). As showed in Figs.…”
Section: Discussionmentioning
confidence: 93%
“…Similarly, the mean shoot dry weight of the sweet corn was 220 g per plot due to the EFB biochar application, while that of the control (without biochar) was 50 g per plot (Abdulrazzaq et al, 2015). Bakar et al (2015) reported that the maximum height of rice, number of panicles/hill, weight of 1000 grains, and total biomass/hill were 22.20, 163, 52.53, and 318.60 % more than the control, respectively using 40 tonnes/ha EFB biochar in a pot study on the effects of EFB biochar on the growth performance of rice.…”
Section: Crop Response To Fresh Fruit Solid Wastes Biocharmentioning
confidence: 98%
“…High drained upper limit enhances the soil aeration potential. Bakar et al (2015) reported that the soil available P, and exchangeable Ca increased by 41, and 37 % more than the control, respectively using 40 tonnes/ha EFB biochar in a pot study on the effects of EFB biochar on the growth performance of rice. Lee et al (2017b) reported that the application of 20 Mg/ha EFB biochar increased soil exchangeable Ca, K and Mg, and cation exchange capacity significantly by 45.45, 343.4 and 72.73, and 3.14 % more than the control (no biochar), respectively.…”
Section: Effects Of Ash and Biochar From Fresh Fruit Bunch Wastes On mentioning
confidence: 99%
“…The empty fruit bunch serves as mulch material and too can be composted and used as organic fertilizer. It has also found use as a feedstock for high-quality biochar (Idris et al, 2014;Bakar et al, 2015;Rozhan et al, 2015). The empty bunch, when burnt, can be used to make local soap.…”
Section: Socio-economic Attributes Of the Oil Palmmentioning
confidence: 99%